2017
DOI: 10.1111/scs.12405
|View full text |Cite
|
Sign up to set email alerts
|

The quality of information received by parents of children with chronic ill health attending hospitals as indicated by measures of illness uncertainty

Abstract: As only 5% of all participants reported low levels of uncertainty this should be of major concern as both an indicator of the quality of communication between health professionals and parents, and of the adverse health effects and poor quality of life experienced by parents of patients with chronic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Low SOC was also associated with negative outcomes such as emotional problems, conduct problems, peer relationship problems, low self‐efficacy, poor adherence to treatment and frequent health complications at school. These results are consistent with existing evidence that suggests that the manageability/comprehensibility of illness and life with illness may influence quality of life and coping among adolescents with long‐term health conditions (Al‐Yateem, Docherty, Altawil, et al, 2017; Nogueira et al, 2009; Tiggelman et al, 2014). Interventions such as teaching skills to manage illness (Barton et al, 2003), cognitive behavioural therapy (Kashikar‐Zuck et al, 2013) and improving SOC (Elfassi et al, 2016; Elissa et al, 2020; Moksnes & Haugan, 2015; Tiggelman et al, 2014; Viswanath & Krishna, 2015) improved coping and boosted psychosocial resources among children and adolescents and were effective in reducing symptoms and psychological distress.…”
Section: Discussionsupporting
confidence: 91%
“…Low SOC was also associated with negative outcomes such as emotional problems, conduct problems, peer relationship problems, low self‐efficacy, poor adherence to treatment and frequent health complications at school. These results are consistent with existing evidence that suggests that the manageability/comprehensibility of illness and life with illness may influence quality of life and coping among adolescents with long‐term health conditions (Al‐Yateem, Docherty, Altawil, et al, 2017; Nogueira et al, 2009; Tiggelman et al, 2014). Interventions such as teaching skills to manage illness (Barton et al, 2003), cognitive behavioural therapy (Kashikar‐Zuck et al, 2013) and improving SOC (Elfassi et al, 2016; Elissa et al, 2020; Moksnes & Haugan, 2015; Tiggelman et al, 2014; Viswanath & Krishna, 2015) improved coping and boosted psychosocial resources among children and adolescents and were effective in reducing symptoms and psychological distress.…”
Section: Discussionsupporting
confidence: 91%
“…Parents of newly diagnosed cancer children reported emotional experiences such as shock, fear, hopelessness, and feeling overwhelmed (Benedetti et al, 2014 ; Lewandowska, 2021 ). In addition, parents feel guilty for blaming their child’s illness on their actions and are concerned about their child’s future (Al Yateem et al, 2017 ). On the other hand, uncertainty changes over time and is accompanied by negative emotions, making unpleasant events more unpleasant (Bar-Anan et al, 2009 ).…”
Section: Concept Analysis Of Uncertaintymentioning
confidence: 99%
“…Negative coping refers to using fear, escape, and other emotions to deal with pressure, allowing things to develop further, and inability to find ways to solve the problem, which increases the malignant development of stressful events[ 6 ]. Some previous research has shown that coping styles can improve patients’ abilities to seek social support and overcome negative emotions, such as depression[ 7 ]. During stroke patients’ treatment and rehabilitation, an active coping style can help them confront their illness more proactively and promote long-term resilience.…”
Section: Introductionmentioning
confidence: 99%